2020
DOI: 10.1101/2020.04.13.20063198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude, practice and perceived barriers among healthcare professionals regarding COVID-19: A Cross-sectional survey from Pakistan

Abstract: Coronavirus disease (COVID-19) is a highly transmittable infection and Pakistan faces sudden hike in number of positive cases including number of healthcare professionals (HCPs) also acquired infection. Knowledge, attitude, and practice survey provides a suitable format to evaluate existing programs and to identify effective strategies for behavior change in society. Therefore, the aim of study is to assess knowledge, attitude and practice among HCPs in Pakistan regarding COVID-19. An online survey-based study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
175
19
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(281 citation statements)
references
References 22 publications
69
175
19
8
Order By: Relevance
“…This may be because the study was conducted during the early stage of an outbreak of this disease when the entire health system and healthcare workers were being prepared to deal with a possible epidemic of COVID-19 in Nepal. The findings were similar to a study done by Saqlain et al, where 93.2% of respondents had good knowledge, positive attitude, and 88.7% of them had good practice towards COVID-19 (9). Similarly, Zhou et al also reported that the majority of HCWs in a study in China had sufficient knowledge and good practice towards COVID-19 (n = 89%, 89.7%, respectively) (10).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This may be because the study was conducted during the early stage of an outbreak of this disease when the entire health system and healthcare workers were being prepared to deal with a possible epidemic of COVID-19 in Nepal. The findings were similar to a study done by Saqlain et al, where 93.2% of respondents had good knowledge, positive attitude, and 88.7% of them had good practice towards COVID-19 (9). Similarly, Zhou et al also reported that the majority of HCWs in a study in China had sufficient knowledge and good practice towards COVID-19 (n = 89%, 89.7%, respectively) (10).…”
Section: Discussionsupporting
confidence: 86%
“…A similar positive correlation between attitude and practice scores was also seen in a study regarding COVID-19 by Peng et al (r = 0.319, p value < 0.001) (11). Saqlain et al also reported positive linear correlation between knowledge and practice scores (r = 0.142, p value-0.016), and between attitude and practice scores (r = 0.174, p value-0.004) in their study (9). The right knowledge, along with the right attitude, can eventually lead to safe practices and healthy behaviors (12).…”
Section: Discussionsupporting
confidence: 72%
“…It is lower than the study conducted in China among health care workers in which the knowledge of HCW towards COVID 19 prevention was high (89%) (Zhou et al 2020). Furthermore, this finding is lower than the finding conducted in Pakistan in which the knowledge towards COVID 19 prevention was 92.3% (Saqlain et al 2020). This discrepancy could be due to the difference in the study population.…”
Section: Discussioncontrasting
confidence: 70%
“…For attitudes about pandemics, worry/fear/helplessness about pandemic (13, 14, 22, 28, 31, 33, 49, 51, 52, 60, 61, 63, 65, 68, 72, 76-78, 81, 83, 84), confidence in governments' ability to manage pandemic (13,23,28,30,33,41,61,63,65,68,70,77,78,82) and perceived severity of infection as a public health problem (13,29,39,41,44,45,59,65,70,72) was most commonly assessed. (Table 3) For practices in pandemics, behaviours related to mask utilization (14,16,23,26,28,30,32,33,35,38,40,48,59,61,63,65,70,73,80,82,(84)(85)…”
Section: Themes Identified From Items Used In Health Literacy Questiomentioning
confidence: 99%
“…Sociodemographic factors which were commonly associated with better health literacy included higher educational level (23, 26, 27, 33, 34, 36, 37, 39, 40, 42, 43, 45, 72-77, 80-82, 88, 89), increased age (23,26,30,37,40,43,48,50,63,65,72,74,75,78,84,85) and female gender (13,16,23,26,33,34,38,40,41,44,45,60,62,72,74,78,80,81,84,85,89). For health systems-based factors, increased experience in the healthcare system (48,56,63,76,77,89) and attendance in health education programs (28,33,58,60,71,<...>…”
Section: Determinants Of Health Literacymentioning
confidence: 99%